KAJIAN TENTANG PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI KECAMATAN CIBUAYA KABUPATEN KARAWANG - Enjang Sudarman (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2018)
Research Title: Study on Behavior Leadership Principal and School Cultural Against Teacher Performance in Cibuaya Public Elementary Schools of District Karawang regency. The purpose of this study: (1) To know the effect the behavior of school leadership on the Teachers Performance in Cibuaya State Primary School of District Karawang regency. (2) To know the effect of school culture on the Teachers Performance in Cibuaya State Primary School of the District Karawang Regency. (3) To know the effect of behavior of school leadership and school culturesimultaneously on the Teachers Performance o in Cibuaya State Primary School of the District Karawang Regency.Using descriptive survey research methods with teachers as much as 52 the population used as samples. The results were obtained: (1) There is a significant effect between Principal Leadership variables (X1) to teacher performance variable (Y). This is evidenced by the results of hypothesis test obtained value t t table (5.581 2.004). partially there is significant effect between the leadership of the principal to teacher performance. (2) There is a significant effect between the variables of school culture (X2) on teacher performance variable (Y). This is evidenced by the results of hypothesis test obtained value t t table (2.50 2.004) partially no significant effect between school culture with teacher performance. (3) There is a significant effect between school leadership and school culture with the same on teacher performance. This is evidenced by ANOVA test obtained F count 23.056 Values greater than 2,004 F table. Donations influence of independent variables (school leadership and school culture) to the dependent variable (performance of teachers) amounted to 45.6%. Or variations of the independent variables used in the model (school leadership and school culture) able to explain 45.6% of the variation of the dependent variable (performance of teachers). While the remaining 54.4% influenced or explained by other variables not included in this research model.